Mujahadah Kamis Wage at Nahdlatul Ulama (NU) Sunan Pandanaran Islamic Boarding School Viewed from Edmund Husserl’s Phenomenological Perspective - Annisa Fadlilah (Lakpesdam PCNU Kota Salatiga, 2021)
Mujahadah Kamis Wage, organized by Sunan Pandanaran Islamic Boarding School. It is a religious tradition closely related to NU teachings where there is a teaching to send prayers for parents who have died. Mujahadah Kamis Wage was held to commemorate the death of one of the founders of the Islamic boarding school, namely Nyai Hj. Jauharoh Munawwir died on Kamis Wage. This tradition is a religious phenomenon whose existence can be investigated from all sides. In this study, the Phenomenology of Edmund Husserl is the author’s point of view in conducting research. Phenomenology can be used to examine phenomena that occur in a religion, such as ways of worshiping, certain rituals, myths that develop, or the spiritual experiences that followers of religion get after performing certain rituals or worship. Edmund Husserl’s phenomenology consists of several steps: Epoche (the act of letting go of oneself), eidetic vision or making ideas, or eidetic reduction by finding the phenomenon’s essence and ignoring aspects that are not important. The last step to reach the essence of an object is by transcendental reduction, which leads the researcher to find another picture of the phenomenon beyond the pre-conception limits. This study indicates that the NU tradition phenomenon at Sunan Pandanaran Islamic Boarding School in the form of Mujahadah Kamis Wage is not only limited to the value of religiosity whose implementation relies on religious teachings, but also the social and economic dimensions that go beyond pre-conceptions depending on who follows and interprets it.